Studying the Possible Factors Influencing the Physical Characteristics of Abnormal Vaginal Discharge and Their Correlation with the Type of Pathogens - Inas Khalid Kadhim; Mohannad Mohsin Ahmed; Zuhair Hameed Abood (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background/aims:Abnormal vaginal discharge is a frequent conditions females at different age groups. It presents with variable physical characteristics and could be attributed to several conditions.The aim of this study is to assess the possible correlation between physical characteristics of vaginal discharge with the type of microbial infection. Methods: The study was conducted from March 2023 to April 2024. All patients were attendents to Al-Kafeel Specialized Hospital or Obstetrics and Gynecology Teaching Hospital in Kerbala, or private consultation clinics. Kerbala, Iraq. All patients had abnormal vaginal discharges and two high vaginal swabs (HVS) were collected during colposcopy by Gynecologist.The first swab was used for amsel,s criteria.The Second Swab was used for microbial culture. Demographic data and the physical characteristics of the discharges were recorded using a specific form (some by personalinterview and others by electronic communications). Results:Out of 244patient’s complained of vaginal discharge. 238(97.5%) had positive culture. majority (49.6%) of them were falling in the age range (26 -35) years, About 96.2% were married and most (73.1%)are education (university or secondary), in most cases (58.4%) the discharge was mucoid and sticky.foul odor was reported in most of cases (59.7%).The most common color 156 out 238, (65.5%) of vaginal discharge was white.The prevalence of AV, BV and VVC among women was (84.8%), (1.68%), (28.57%), respectively. Conclusion: Aerobic vaginitis (AV) andvulvovaginal candidiasis (VVC) are the common causes of vaginitis in Iraqi women.